A Meta-Analysis on the Effect of Oil Palm Fronds As Small Ruminant Feed - Fhonna, Fenda Alvionita; Samadi, Samadi; Jayanegara, Anuraga; Wajizah, Sitti; Samsudin, Anjas Asmara (Fakultas Peternakan, Universitas Padjadjaran, 2025)
Oil Palm fronds (OPF) as the main waste of oil palm plantations have considerable promise as a small ruminant feed. Unfortunately, due to the diversity of previous findings, a clear response pattern has still to be determined. For this reason, in the present study, meta-analysis was employed to synthesize existing findings regarding the effect of OPF as a small ruminant feed. The database was constructed using data from ten published articles that fit the inclusion criteria. The applied statistical model was a mixed model. Findings revealed no significant effect (P>0.05) of OPF inclusion on nutrient intake, nutrient digestibility, animal performance, and nitrogen utilization. Despite this, there was a tendency for dry matter intake (DMI) to increase and average daily gain (ADG) to decrease with the greater presence of OPF in the feed. The insignificance of the present findings suggests that OPF can be included in small ruminant feed without causing significant negative effects.